Knee Osteoarthritis Risk Is Increased Five-Fold After Knee Injury In Indonesian National Police Mobile Brigade Corps - Nugrahana, Raisa Yunika; Supartono, Basuki; Makkiyah, Feda Anisah; Heristyorini, Ayodya (Universitas Wijaya Kusuma Surabaya, 2025)
Abstract Background: Knee osteoarthritis (OA) is a globally alarming condition that is closely related to mechanobiological factors. Based on several previous studies, it is known that knee OA is correlated with knee injury and that play an important role in the expansion of knee OA. Objective: This research aims to find out the relationship between knee injury history with knee OA severity and to estimate the risk of knee OA after knee injury. Methods: This research used observational analytical methods with a retrospective hospital-based cohort study design. Using consecutive sampling technique. The total research sample was 68 participants who Indonesian National Police Mobile Brigade Corps had knee OA period January 1 2021-December 31 2023 at the RS Bhayangkara Tk. I Pusdokkes Polri Jakarta. Result: There was a significant relation between knee injury history with knee OA severity (p = 0.011) and odds ratio 5.0 (95% CI: 1.6-15.9). Characteristics of members of the Indonesian National Police Mobile Brigade Corps with the highest risk of knee OA, namely in the pre-elderly with an age range of 45 - â‰¤ 59 years (66.2%), female (51.5%), work unit of the Headquarters Mobile Brigade Corps (45.6%), had a history of knee injury (70.6%), with mild degrees (1-3) (73.5%), and the majority experienced anterior cruciate ligament (ACL) injury (23.5%). Conclusion: The study concluded that there was a statistically significant relation between knee injury history with knee OA severity and that the risk of developing knee OA increased fivefold after knee injury.